2013
DOI: 10.1128/cvi.00225-12
|View full text |Cite
|
Sign up to set email alerts
|

On the Efficacy and Safety of Vaccination with Live Tachyzoites of Neospora caninum for Prevention of Neospora-Associated Fetal Loss in Cattle

Abstract: bInfection of cattle with Neospora caninum may result in abortion or the birth of a congenitally infected calf. Vaccination with live N. caninum protects against experimental infection of cattle and mice, and the naturally attenuated Nc-Nowra strain of N. caninum is of particular interest as a potential vaccine candidate. Vaccination of heifers prior to breeding with live Nc-Nowra tachyzoites by either the subcutaneous or the intravenous route reduced the rate of abortion and the presence of the parasite in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 20 publications
3
41
0
3
Order By: Relevance
“…In another study, it was demonstrated that live vaccination protects against fetal death, all cows immunized intravenously 9 weeks prior to artificial insemination and challenged at 70 days of pregnancy had viable no infected offspring (Williams et al, 2007). Partial protection effect against infection of the offspring, varying from 25.9% to 85.2% depending on the route of vaccination and growth conditions of the parasites, had been shown when cows were vaccinated at 63-75 days before pregnancy and challenged at 139 days of pregnancy (Weber et al, 2013). Compared to these studies, our design differs because vaccination was performed at mid-term under field conditions where the dams were seropositive following natural infection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In another study, it was demonstrated that live vaccination protects against fetal death, all cows immunized intravenously 9 weeks prior to artificial insemination and challenged at 70 days of pregnancy had viable no infected offspring (Williams et al, 2007). Partial protection effect against infection of the offspring, varying from 25.9% to 85.2% depending on the route of vaccination and growth conditions of the parasites, had been shown when cows were vaccinated at 63-75 days before pregnancy and challenged at 139 days of pregnancy (Weber et al, 2013). Compared to these studies, our design differs because vaccination was performed at mid-term under field conditions where the dams were seropositive following natural infection.…”
Section: Discussionmentioning
confidence: 94%
“…It has been considered that an effective vaccine against neosporosis should either be aimed to prevent infection in uninfected animals, or to prevent abortion or vertical transmission in infected animals (Innes et al, 2002). Previous studies demonstrated that vaccination of naïve cows with live tachyzoites was protective against experimental challenge (Williams et al, 2007;Rojo-Montejo et al, 2013;Weber et al, 2013;Hecker et al, 2013;Reichel et al, 2014;Monney and Hemphill, 2014). The Israeli N. caninum NcIs491 isolate, obtained from brain tissue of an aborted fetus, can be easily grown in culture and is suggested to be of low pathogenicity to laboratory animals including gerbils (Fish et al, 2007) and mice (unpublished results), in comparison with the NC-1 strain (Lindsay et al, 1995;Rettigner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In three cattle studies (Williams et al, 2007(Williams et al, , 2000Innes et al, 2001), where the dams were inoculated with live tachyzoites prior to mating, there was no evidence of vertical transfer to the calves using serology, immunohistochemistry and PCR for the detection of N. caninum infection. In contrast, low levels of abortion or detection of N. caninum have been reported in 3 other studies where cows were inoculated prior to pregnancy (Weston, 2011;Hecker et al, 2013;Weber et al, 2013). Thus, protection against vertical transmission in cattle following inoculation prior to pregnancy is not absolute.…”
Section: Discussionmentioning
confidence: 56%
“…Hope had been expressed that efficacious and economically viable vaccines would become available for the control of N. caninum infections and abortions when, in addition to a commercially available inactivated vaccine (Neoguard™), highly efficacious live vaccine candidates showed promise Weber et al 2013). However, these vaccine candidates may yet be a few years from reaching the market place.…”
Section: Introductionmentioning
confidence: 98%